Strategi Komunikasi Pemasaran Pada Baso Aci Tulang Rangu Albara Melalui Instagram - Khoirunnisa, Hasna; Dharta, Firdaus Yuni; Poerana, Ana Fitriana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Marketing communication strategies are always carried out by business people, therefore marketing communication strategies are an important aspect for a business so that these businesses can achieve sales targets. This research is entitled Marketing Communication Strategy for Baso Aci Tulang Rangu Albara. The purpose of this study was to find out how the marketing communication strategy carried out by Baso Aci Albara using social media Instagram. The research method used is a qualitative method with a qualitative descriptive approach. The result of this research is that Baso Aci Albara has succeeded in using Instagram social media to carry out its marketing activities, as well as achieving the consumer target desired by Baso Aci Albara.